2021
DOI: 10.1186/s12978-021-01091-1
|View full text |Cite
|
Sign up to set email alerts
|

“As a woman who watches how my family is… I take the difficult decisions”: a qualitative study on integrated family planning and childhood immunisation services in five African countries

Abstract: Background Family planning (FP) has the potential to improve maternal and child health outcomes and to reduce poverty in sub-Saharan Africa. However, substantial unmet need for modern contraceptive methods (MCMs) persists in this region. Current literature highlights multi-level barriers, including socio-cultural norms that discourage the use of MCMs. This paper explores women’s choices and decision-making around MCM use and examines whether integrating FP services with childhood immunisations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Evidence demonstrating fear of side effects and its role as a barrier to MCM uptake is common in the literature. Studies from India, Nepal, Nigeria, Uganda and the Philippines all show that fear of side effects can be a major barrier to MCM uptake 40–43. Studies that have assessed community myths about MCMs and how they lead to fears about side effects and resistance to MCMs have suggested that social norms play a large role in influencing individual-level choices about MCM use.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence demonstrating fear of side effects and its role as a barrier to MCM uptake is common in the literature. Studies from India, Nepal, Nigeria, Uganda and the Philippines all show that fear of side effects can be a major barrier to MCM uptake 40–43. Studies that have assessed community myths about MCMs and how they lead to fears about side effects and resistance to MCMs have suggested that social norms play a large role in influencing individual-level choices about MCM use.…”
Section: Discussionmentioning
confidence: 99%
“…These barriers have been widely described in the literature [ 2 , 32 ] and reflect the symptoms of patriarchal structures within which women make reproductive decisions [ 3 ]. In the context of SRH empowerment these external factors, combined with women’s internal motivations, shape fertility desires and ambitions [ 6 , 12 ]. Women engaged in CCU when they believed their fertility choices were not supported within their relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Unequal gender-based power relations have emerged as a key constraint on woman’s reproductive health decision-making [ 3 ]. In particular, male reproductive preferences and disapproval of FP have been found to drive reproductive outcomes, including the use of modern contraceptive methods and family size [ 4 6 ]. To overcome these constraints, some women choose to engage in covert contraceptive use (CCU), that is contraceptive use without their husband’s knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies from Ethiopia also assessed FP integration with MCH services and reported on its effectiveness. Studies on the effect of FP integration with HIV care services reported improvement in FP uptake and declines in unmet need for FP among women of reproductive age group with HIV infection (13,14). A longitudinal study also demonstrated that FP counselling during postpartum and during child immunization period were associated with increased modern contraceptive uptake (15).…”
Section: Introductionmentioning
confidence: 98%